Botanic Garden Profile: The National Botanic Garden of Wales at 20 - Ritchie, Will (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2021)
The National Botanic Garden of Wales celebrated its 20th anniversary in 2020 with many achievements and challenges for staff, volunteers and stakeholders to reflect upon. An ambitious project since its inception, the Botanic Garden has grown from humble beginnings into an established national institution in its first two decades, with the tireless efforts of many helping it to flourish. Early proponents of the idea did much to foster others’ support, and what started as a vision shared between a small group of enthusiasts became a Millennium Commission funded project in 1996. Since opening to the public in 2000, much work has been done to create the gardens, infrastructure and teams necessary to pursue the Botanic Garden’s mission. In a climate of increasing biodiversity loss and environmental degradation, science, horticulture and education programmes have been developed which continue to make tangible contributions to the study, conservation and interpretation of plant diversity in Wales and beyond. With 568 acres (230 ha) to develop further still and world-class facilities such as the Great Glasshouse, the Botanic Garden aims to play an important role in research, conservation, education and public engagement for many years to come.